Prevalence of Extended Spectrum Β-Lactamase (ESBL) and Quinolone Non-susceptible (QNS) Enterobacteriaceae in Inpatient and Outpatient Settings in the USA from 2011–2016. (4th October 2017) - Puttagunta, Sailaja; Gupta, Vikas; Murray, John; Dunne, Michael
Abstract: Background: Rising rates of resistance to quinolones and cephalosporins have been reported recently amongst E.coli and other Gram-negative pathogens that cause urinary tract infections (UTI). We sought to define the regional prevalence of quinolone-non-susceptible (QNS) and extended spectrum β-lactamase (ESBL) producing Gram-negative pathogens in the United States (US). Methods: An electronic research dataset of Becton, Dickinson and Company from 213 US hospitals was analyzed to study trends in prevalence of QNS and ESBL organisms from 2011 to 2016. All non-duplicate Escherichia coli, Klebsiella pneumoniae and Proteus mirabilis isolates were characterized as ESBL if confirmed as ESBL-positive per commercial panels or intermediate/resistant to either ceftriaxone, cefotaxime, ceftazidime or cefepime and categorized as QNS if identified as intermediate or resistant to either ciprofloxacin or levofloxacin Isolates were categorized by specimen collection location as follows: (a) Inpatient if collected in hospitalized patients and (b) Ambulatory: isolates not collected during hospital admission. Results: Overall non-duplicate urine ESBL events increased from 5.1% in Q1 2011 to 8.1% in Q4 2016 where as non-duplicate urine QNS remained steady at 25.7% in Q1 2011 to 24.2% in Q4 2016. There are notable differences for both ESBL and QNS events noted across inpatient and outpatient settings Conclusion: ESBL producing organisms at these sentinel hospitals have been rising since 2011. Quinolone resistance remains persistently elevated. Disclosures: S. Puttagunta, Iterum Therapeu: Employee and Shareholder, Salary. M. Dunne, Iterum Therapeutics: Employee and Shareholder, Salary.